Productive confusion. Questions of hospitality of cultural institutions - Mariya S. Frolova (Управление культурой)
The reader as a format, as a way to give the reader an idea of the complexity and diversity of approaches to understanding various phenomena, is gradually coming out of the shadows again. It is in this form that in the publication we are considering, the editor-compiler gives us the opportunity to discover for ourselves a transdisciplinary and transexperienced view of the concepts of inclusion and diversity in their various manifestations. In particular, how they are implemented in the spaces of museum institutions. The four sections of the reader present materials of various styles and forms on inclusiveness in museums as institutions; topics of disability and its various interpretations, migrant experiences and identities; culture and opportunities for the deaf. In addition to providing information, materials give the reader the opportunity to join a variety of experiences, to implement inclusion in practice.